Brunei Darussalam - Khalid, Madihah; Mohd Salleh, Romaizah (SEAMO REgional Centre for Education in Science and Mathematics, 2010)
In the field of education, the role played by the Information Communication Technology (ICT) in this era of globalisation and information technology is undeniably getting more and more important especially in the teaching and learning of mathematics and science